Eco-Efficiency and Financial Performance: An Evidence from Indonesian Listed Company - Rochmawati Daud; Inten Meutia; Emylia Yuniarti (Universitas Muhammadiyah Surakarta, 2023)
This study uses natural resource-based theory to provide empirical evidence regarding the effect of sustainability policies in the form of emission reductions on the financial performance of companies listed on the Indonesia Stock Exchange. The concept of eco-efficiency is measured using the emission intensity approach. This study uses a period of data panels from 2019 to 2021 to capture the effect of eco-efficiency on the company's financial performance. Using three accounting measures of financial performance in the research model: ROA, ROE, and ROS, to understand in more detail the impact of eco-efficiency on the company's financial performance. We find evidence that eco-efficiency has a positive impact on financial performance. This finding implies that the fewer GHG emissions the company produce, the higher the company's financial performance. This finding has implications as support for companies that emission reduction policies can positively affect the company's financial performance.